Namibia : Technical Assistance Report-The National Accounts Mission. (IMF Staff Country Reports; Country Report, 2018)
This Technical Assistance report discusses the recommendations made by the IMF mission to support the Namibia Statistics Agency (NSA) in improving national accounts statistics for decision making. At present, NSA produces quarterly estimates of GDP in constant prices using a variety of indicators, some of which are sub-optimal. The IMF mission worked with the national accounts team to identify appropriate data for industries where value-added tax turnover would not be usable. For the insurance industry, the IMF mission described the conceptual framework and suggested possible data. The NSA will work with the insurance regulator to discover what data can be made available.